Empagliflozin alters lipid metabolism in the myocardium and liver in a prediabetes model with severe dyslipidemia - Miklankova, Denisa; Markova, Irena; Hüttl, Martina; Malinska, Hana (Frontiers in Pharmacology, 2024)
Recent studies suggest that empagliflozin reduces total and cardiovascular mortality in both diabetic and nondiabetic subjects. Although the exact mechanism is unclear, it is understood to positively affect myocardial energetics, including the metabolism of ketone bodies, lipids, and fatty acids. In this study, we compared empagliflozin effects on lipid metabolism in the heart and liver in a prediabetic rat model with severe dyslipidemia. Materials and methods: Wistar rats served as the control group, while hereditary hypertriglyceridemic (HHTg) rats were used as a nonobese, prediabetic model. Rats were treated with or without empagliflozin at a dose of 10mg/kg body weight (BW) for eight weeks. Results: In HHTg rats, empagliflozin decreased body weight and adiposity, improved glucose tolerance, and decreased serum triacylglycerols (TAGs) (p < 0.001). Empagliflozin decreased the activity and gene expression of the lipogenic enzyme SCD-1 (p < 0.001) in the myocardium, which may have led to a decrease in the ectopic accumulation of TAGs and lipotoxic diacylglycerols and lysophosphatidylcholines (p < 0.001). Changes in the myocardial phosphatidylcholine/phosphatidylethanolamine ratio (p < 0.01) and in the fatty acid profile of myocardial phospholipids may have contributed to the antifibrotic effects of empagliflozin. The antiinflammatory effects of empagliflozin were evidenced by an increased IL-10/TNF ratio (p < 0.001), a marked decrease in arachidonic acid metabolites (20-HETE, p < 0.001), and an increase in PUFA metabolites (14,15-EETs, p < 0.001) in the myocardium. However, empagliflozin did not significantly affect either the concentration or utilization of ketone bodies. In the liver, empagliflozin decreased lipogenesis and the accumulation of TAGs and lipotoxic intermediates. Its effect on arachidonic acid metabolites and alterations in n-3 PUFA metabolism was less pronounced than in the myocardium.Our findings suggest that empagliflozin treatment in the heart and liver reduced the accumulation of neutral lipids and lipotoxic intermediates and altered the metabolism of n-3 PUFA. In the heart, empagliflozin altered arachidonic acid metabolism, which is likely associated with the Running Title 2 anti-inflammatory and antifibrotic effects of the drug. We assume that these alterations in lipid metabolism contribute to the cardioprotective effects of empagliflozin in prediabetic states with severe dyslipidemia.